Nutritional adequacy and the role of supplements in the diets of Indigenous Australian women during pregnancy. (February 2021) - Beringer, Madison; Schumacher, Tracy; Keogh, Lyniece; Sutherland, Kathryn; Knox, Paris; Herden, Jodie; Brown, Leanne; Rae, Kym
Highlights: Few Indigenous women met national nutrient recommendations. Supplement use contributes significantly to nutritional adequacy. Core foods and beverages are nutrient-dense contributors to adequacy Non-core foods and beverages contain some essential nutrients Abstract: Objective: To determine sources of key nutrients contributing towards nutritional adequacy during pregnancy (fibre, calcium, iron, zinc and folate) in a cohort of women carrying an Indigenous child. Design: Analysis of cross-sectional data from a prospective longitudinal cohort study that followed Indigenous women through pregnancy. Setting: Women recruited via antenatal clinics in regional and remote locations in NSW, Australia as part of the Gomeroi gaaynggal project. Participants: One hundred and fifty-two pregnant Australian women who identified as Indigenous or carrying an Indigenous child. Measurements and Findings: Measurement outcomes included demographic information, smoking status, anthropometrics (weight and height, ), self-reported pre-pregnancy weight, health conditions and dietary information (24-hour food recall). Findings indicate the inadequate intake of key pregnancy nutrients in this cohort. Supplements contributed to the nutrient adequacy of the cohort with 53% reporting use. As expected, predominant sources of fibre were from core food groups, whereas calcium was attained from a range of sources including food and beverages, with small amounts from supplementation. Importantly, supplements contributed significant amounts of iron, zinc and folate. Key Conclusions: There is limited literature on Indigenous Australian maternal nutrition. This study highlights the key dietary contributors of nutritional adequacy during pregnancy for the cohort and that supplementation may be considered a viable source of nutrients during pregnancy for these women. Few women met national nutrient recommendations. The findings present an opportunity to optimise nutrient intakes of Indigenous pregnant women. Implications for practice: Culturally appropriate targeted interventions to optimise dietary intakes of Indigenous Australian pregnant women is required. Collaborative support of health workers, Indigenous Australian communities, dietitians, and researchers to raise awareness of nutrition during pregnancy is imperative to achieving nutrient targets and optimising pregnancy outcomes. Targeted interventions provide positive opportunities to achieve improvements.